(untitled) (International Journal of Engineering and Computer Science, 2018)
In India there are numerous river bridges.Those bridges have the capacity of holding only light weighted vehicles.The heavy vehicles are restricted to use those bridges.Those bridges are seen just with a warning board alone.But in most cases the drivers of the heavy vehicles may violate the rules and they may use the same bridge to cross the river.This can result in the development of cracks in the bridge which eventually causes the bridge to collapse.In Mahaath of Maharastra,a river bridge over the Savitri river collapsed weeks ago.The reason has found out be the entry of heavy vehicles on the bridge.To prevent the entry of heavy vehicles to the river bridges,an arch is built over the entrance of the bridge in some places across India.But this can increase the dead load on the bridge and this could further reduce the strength of the bridge.Thus a smart system which prevents the entry of heavy vehicles into the river bridges is proposed in this paper.This system uses a automatic checkpost in the entrance of the bridge.The weight sensor is placed on the entrance of the bridge.The vehicles when stopped at the entrance of the bridge,the weight sensor which is installed down at the road determine the weight of the vehicle being stopped at that moment.If the weight exceeds the threshold value,the entry of heavy vehicle can be found.The GSM Module is used to alert the concerned personnel.The buzzer is installed in the nearby traffic control office which sounds when the rules are violated in this case.When the entry of heavy vehicles is found,the checkpost will remain closed.In other cases the checkpost will open.This system reduces the manpower and it makes the surveillance completely automatic.This system if implemented can reduce the bridge collapses.